Pengembangan Game Android Pada Anak Menggunakan Pendekatan User Centered Design Dan Evaluasi Usability Think Aloud - Alvico, Alvico; Kurniawan, Dedy; Meiriza, Allsela; Syahbani, Muhammad Husni; Firnando, Ricy (AI Society & STMIK Indonesia, 2025)
Technology, especially handheld devices, has become an integral part of modern life. The use of handheld devices among children aged 12-15 years reaches 99.61%. Despite the potential to cause dependency, these devices can be utilized positively, for example through learning with educational games. One of them is a titungan game that aims to increase user motivation and skills. However, the development of this game must also consider user needs. This research applies the User Centered Design method to improve the experience and comfort of playing, and the Think Aloud method as an evaluation. This study involved 8 participants consisting of children with an age range of 10-14 years. The results showed that the developed application has met the needs of users, with only two problems identified from 64 total evaluation scenarios with a percentage of 96.87% using the Think Aloud method.